Parâmetros hidrossedimentológicos da bacia hidrográfica do São José, no Cariri cearense - Costa, Kassius Vinissius de Morais (2013)
This study aimed to analyse the São José river catchment (BHSJ) hydrosedimentological parameters, evaluate the sediment yield and define the susceptibility of soils to erosion based on the Equation Universal Soil Loss (USLE). Therefore, it was determined: (i) the rainfall erosivity (R - factor) at catchment, based on the formulations proposed by Wischmeier and Smith (1958) and Fournier (1960), (ii) the soil erodibility (K – factor) at catchment, it was calculated using the nomograph developed by Wischmeier et al. (1971), (iii) the topographic factor (LS – factor) was obtained through the method of Bertoni and Lombardi Neto (1990), using the Digital Elevation Model (DEM) generated by the Shuttle Radar Topography Mission (SRTM), (iv) identification, delineation and description of the land cover (C – factor), using GIS, through by the classification techniques of multitemporal satellite images. The sediment delivery ratio (SDR) of the catchment was estimated based in equations proposed by Maner (1958), Roehl (1962), Vanoni (1975), Renfro (1975) and Williams and Brendt (1972). The equation that presented the best fit was selected, comparing modelled and measured data at the catchment outlet, for hydrological year monitored since September 2011 to September 2012. The results show the following: (i) the rainfall erosivity, determined by the equation developed in this study and validated with Nash and Sutcliffe coefficient of 0.81; presented satisfactory results in the adjustment of the USLE equation for BHSJ, with best adjustments among the compared methods, that presented percentage errors of at least 50%; (ii) the soil erodibility determined was spatialized in the catchment by Kriging, using the method of interpolation Gaussian model tested and validated; (iii) the topographic factor was determined and spatialized in the catchment, considering average values for six distinct classes of slopes; (iv) the use types and occupation of the basin were divided into agriculture, caatinga, cerrado, tropical rainforest, bare soil, urban and undergrowth. In the catchment, the rate of erosion was estimated at 364 t ha-1.year-1 from the USLE, corresponding to a sediment yield of 1.48 x 106 t in the hydrological year. The map of erosion susceptibility showed that the degree of erosion basin presented: low, medium, high and very high, respectively, 26.39, 34.34, 30.37 and 8.90% of the area. SDR determined by the equations proposed by Maner (1958) and Vanoni (1975) presented values near suspended sediment discharge measured at the catchment outlet during the monitored events, with percentage errors of -12.4 and -2.6%, respectively.